Comparative morphometric analysis of vermilion border epithelium and lip epidermis - Lanfranchi, Héctor E.; Molinari de Rey, Beatriz L. (1978)
Fil: Lanfranchi, Héctor E. Comisión Nacional de Energía Atómica; Argentina